A Comparative Study on Financial Performance of Private and Public Setor Bank in Ethiopia With Special Reference to Affecting Factors and their Impact on Performance Indicators - Worku, Seifu Eshetu (The journal of contemporary issues in business and government, 2022)
This paper discovers a comparative Study on Financial Performance of Private and Public Sector Bank in Ethiopia with Special Reference to Affecting Factors and Their Impact on Per- formance Indicators. This study uses different econometric methods. This research is mainly based on secondary data, appropriateness and availability of data is very important for carried out this research. Data collection design consists of planning for collecting required data from adequate source. Population: For this research work, population consists of all 26 pri- vate sector banks and all 2 State Owned banks or Public Banks working in Ethiopia during financial year 2002 - 2013. Sample: As this research work is based on secondary data all 26 private sector banks and all 2 State Owen banks has been selected as a sample. So in this re- search census has been studied rather than sample. Time Frame: Secondary data for selected parameters of all private and State Owned banks has been collected for last 12 year i. e. from year 2002 to 2013. The Partial result of study indicate that Private sector banks performance is good compare to public sector banks in terms of capital adequacy ratio (level – I) , Public sector banks performance is good compare to private sector banks in terms of capital ade- quacy ratio (level – II) and This research work is completely based on secondary data, which may be extended by taking views of top level employees of banks on financial performance of banks, which may help researcher to identify factors responsible for difference in financial performance of banks.